Effect of CSF1R inhibitor on glial cells population and remyelination in the cuprizone model. (October 2021) - Tahmasebi, Fatemeh; Barati, Shirin; Kashani, Iraj Ragerdi
Abstract: Multiple sclerosis is a kind of autoimmune and demyelinating disease with pathological symptoms such as inflammation, myelin loss, astrocytosis, and microgliosis. The colony stimulating factor 1 receptor (CSF1R) is an essential factor for the microglial function, and PLX3397 (PLX) is its specific inhibitor. In this wstudy, we assessed the effect of different doses of PLX for microglial ablation on glial cell population and remyelination process. Sixty male C57BL/6 mice (8 weeks old) were divided into 6 groups. The animals were fed with 0.2% cuprizone diet for 12 weeks. For microglial ablation, PLX (290 mg/kg) was added to the animal food for 3, 7, 14 and 21 days. Glial cell population was measured using immunohistochemistry. The rate of remyelination was evaluated using electron microscopy and Luxol Fast Blue staining. The expression levels of all genes were assessed by qRT-PCR method. Data were analysed using GraphPad Prism and SPSS software. The results showed that the administration of different doses of PLX significantly reduced microglial cells ( p ≤ .001). PLX administration also significantly increased oligodendrocytes population (p ≤ .001) and remyelination compared to the cuprizone mice, which was aligned with the results of LFB and TEM. Gene results showed that PLX treatment reduced CSF1R expression. According to the results, the administration of PLX for 21 days enhanced remyelination by increasing oligodendrocytes in the chronic demyelination model. These positive effects could be related to the reduction of microglia.